Battlepug: the compugdium ebook The compugdium. - Norton, Mike (Battlepug (2012)., 2019)
At long last, MIKE NORTON's award-winning fantasy/humor webcomic is collected in one volume! Join the last Kinmundian and his faithful steed, The Battlepug, as they travel the globe seeking revenge against every giant ridiculous animal they can find. Featuring extras like sketches and art by some of the most creative artists in the business today! Collects the entire 5-volume original series of BATTLEPUG!. Author: Mike Norton. Illustrator: Mike Norton, Allen Passalaqua . 2019 Mike Norton.